1985
DOI: 10.1172/jci111738
|View full text |Cite
|
Sign up to set email alerts
|

Influence of chronic lactulose ingestion on the colonic metabolism of lactulose in man (an in vivo study).

Abstract: The effects of a chronic load of nonabsorbable sugars on intracolonic bacterial metabolism of carbohydrates and on H2 breath excretion are disputed. However, most of the discussion relies on indirect evidence or on results of in vitro studies. Thus, we attempted to assess directly and in vivo the effects on intracolonic metabolism of lactulose of a chronic oral load of this nonabsorbable disaccharide. 20 g of lactulose was given orally twice daily during 8 d to eight normal volunteers. In all, breath H2 concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
112
0
1

Year Published

1992
1992
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(118 citation statements)
references
References 27 publications
5
112
0
1
Order By: Relevance
“…Digestive tolerance of maltitol A Ruskone-Fourmestraux et al Prolonged ingestion of slowly absorbed sugars, such as lactose and lactulose, results in changes in the metabolic activity of the colonic flora, especially a fall in breath excretion of H 2 , which increases its ability to ferment the sugar (Florent et al, 1985;Flourié et al, 1993;Launiala, 1968;Perman et al, 1981). As a result, there is efficient fermentation of the chronically ingested unabsorbed sugar, and thus a reduction in its diarrhoeogenic effect (Rambaud & Flourié, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Digestive tolerance of maltitol A Ruskone-Fourmestraux et al Prolonged ingestion of slowly absorbed sugars, such as lactose and lactulose, results in changes in the metabolic activity of the colonic flora, especially a fall in breath excretion of H 2 , which increases its ability to ferment the sugar (Florent et al, 1985;Flourié et al, 1993;Launiala, 1968;Perman et al, 1981). As a result, there is efficient fermentation of the chronically ingested unabsorbed sugar, and thus a reduction in its diarrhoeogenic effect (Rambaud & Flourié, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…The capacity to ferment unabsorbable sugars, such as lactose and lactulose, and to reduce their laxative effects can, however, be increased by regular ingestion of these sugars, which results in changes in the metabolic activity of the colonic flora, especially a reduced excretion of hydrogen in the breath (H 2 ) (Florent et al, 1985;Flourié et al, 1993;Launiala, 1968;Perman et al, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…It has even been suggested that a few key microorganisms, present in comparatively small numbers, may have key roles to fulfil in the function of the total microflora [33]. An example of why microbial counts are not necessarily appropriate for the investigation of microflora activity as such, was reported in a study by Florent et al [8]. They measured the effects of an oral load of nonabsorbable sugars, and failed to show any significant modification of the bacterial populations examined, which is in agreement with the findings of Finegold and Sutter [7], and Hentges [15].…”
Section: Microbial Counts Vs Molecular Techniquesmentioning
confidence: 99%
“…This may be due to habituation to the ®ber. 44,46 Several studies examined the effect of ®ber supplementation next to an energy-restricted diet on weight loss. Additional ®ber intake next to a lowenergy diet has been shown to be effective in several studies 20,21 even during long-term treatment, 23 but not in all.…”
Section: Discussionmentioning
confidence: 99%